PENGARUH KEBIJAKAN PEMBIAYAAN DALAM MENINGKATKAN KINERJA KEUANGAN PERBANKAN SYARIAH: STUDI EMPIRIS PADA PERBANKAN SYARIAH DI INDONESIA - Sutrisno Sutrisno (Journal of Management and Business Review, 2017)
The development of Islamic banking in Indonesia is characterized by rapidly increasing assets, third party funds, and financing. Islamic banks as financial intermediaries are required to be able to distribute the funds in the form of financing to communities who need of funds. Due to the funding provided is supposed to increase bank profits. The purpose of this study is to analyze and examine the role of financing decisions to financial performance on Islamic banking. In this study the financial performance measured by return on equity (ROE) and Net Profit Margin (NPM) as the dependent variable, while the independent variables are cinsist of mudharaba financing (MUD), Musharaka financing (MUS), murabaha financing (MUR), Ijara financing (IJR), and qordul hasan financing (QORD). We also use firm size as a control variable. Samples in this study were eight islamic banks in Indonesia. We use multiple regression analyzes with the aid program as E-views, with a significance level of 5%. The results showed that variable of musharaka financing, murabaha financing, and firm size have a significant effect on profitability. While variable of mudaraba financing, ijara financing and qord financing no significant effect on islamic bank performance.